Understanding the influence of green washing on green equity and green purchase intention among electric vehicle consumers in Klang Valley - Heng, Xian Wei (2024)
This study investigates the impact of greenwashing on green brand equity (GBE) and purchase intention (GPI) among electric vehicle (EV) consumers in Klang Valley, Malaysia. Greenwashing, a prevalent issue in green marketing, undermines consumer trust and satisfaction, influencing their loyalty and perceptions of corporate social responsibility (CSR). By integrating corporate legitimacy and signaling theories, this research explores the relationships between greenwashing, green trust, green satisfaction, green brand loyalty, perceived CSR, green brand image, green brand equity, and green purchase intention. A quantitative approach was employed, collecting data from 384 EV consumers via structured questionnaires analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal greenwash significantly influences green brand image, green brand loyalty, green satisfaction, green trust, and perceived CSR, as well as supporting the notion that green brand equity significantly drives purchase intention. The results highlighted the importance of transparency and credible green marketing strategies to enhance brand equity and foster sustainable consumer behavior. This study provides theoretical and practical insights for policymakers and industry take holders to combat greenwashing and promote environmental responsibility in the EV sector.